Black male teachers diversifying the United States' teacher workforce - Lewis, Chance W. (Chance Wayne), 1972-; Toldson, Achebe, 1973- (Bingley, U.K. : Emerald, 2013)
Recently, U.S. Secretary of Education Arne Duncan suggested that placing Black men in the classroom as teachers is a critical need in the American educational system. Many education policymakers and researchers falsely believe that Black male teachers have a primary responsibility to foster the social development of Black male students. However, increasing the presence of Black male teachers improves the diversity of the profession and should be viewed as a benefit to the system, as they provide quality services to all students regardless of race and/or gender. This edited volume offers sound suggestions for advancing diversity in the teaching profession. It provides teacher education programs with needed training materials to accommodate Black male students, and school district administrators and leaders with information to help recruit and retain Black male teachers. Each chapter will feature policy and practice recommendations and a case example to spur action and increase opportunities for discussion.
Black male teachers : diversifying the United States' teacher workforce / Chance W. Lewis, Ivory A. Toldson -- Black male teachers' path to U.S. K-12 classrooms : framing the national discussion / Chance W. Lewis -- Race matters in the classroom / Ivory A. Toldson -- Educating the race in postmodern times : the intraracial border crossings of black male teachers / Brockenbrough Ed -- Recruiting teachers from within : career ladders for paraprofessional educators / Erin Croke, Travis Dale, William Ebenstein -- Teaching across gender : the dynamics of black male teachers and female students / Candice Crowell, Kamilah M. Woodson, Shafeeq Rashid -- The case of a black male mathematics teacher teaching in a unique urban context : implications for recruiting black male mathematics teachers / Julius Davis, Toya Jones Frank, Lawrence M. Clark -- "I can get at these kids" : a narrative study exploring the reasons black men teach / Dawn Nicole Hicks Tafari -- No one told us : recruiting and retaining African American males in the college of education program from the urban and rural areas / Camesha Hill-Carter -- Double-talking : the complexities surrounding black male teachers as both problems and solutions / Tambra O. Jackson, Gloria S. Boutte, Brandy S. Wilson -- Pathways to teaching : the perspectives and experiences of two black male teens considering teaching as a career / Kara Mitchell Viesca, Margarita Bianco, Nancy Leech -- A call for African American male teachers : the supermen expected to solve the problems of low-performing schools / Vivian Gunn Morris, Curtis L. Morris -- Being black, being male, and choosing to teach in the 21st century : understanding my role, embracing my call / Chezare A. Warren -- They deserve it / Justin Newell -- Opportunities to die for / Jamil Alhassan -- Beyond paying lip service to diversity : strategies for recruiting, training, and retaining black male teachers / Khary Golden -- Choosing discipleship over the veil / Randy R. Miller -- African American male teachers and the school leadership pipeline : why more of these best and brightest are not principals and superintendents / Leslie T. Fenwick, Chike Akua -- Exploring the relationship between academic self-regulation and educational outcomes among African American male education majors / Lamont A. Flowers.
Keywords: Education -- Multicultural Education; Teaching staff; Teachers, Black -- United States; African American teachers -- United States; Multicultural education -- United States